2020
DOI: 10.1101/2020.11.17.386979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Multiplex” rheostat positions cluster around allosterically critical regions of the lactose repressor protein

Abstract: Amino acid variation at “rheostat” positions provides opportunity to modulate various aspects of protein function – such as binding affinity or allosteric coupling – across a wide range. Previously a subclass of “multiplex” rheostat positions was identified at which substitutions simultaneously modulated more than one functional parameter. Using the Miller laboratory’s dataset of ∼4000 variants of lactose repressor protein (LacI), we compared the structural properties of multiplex rheostat positions with (i) “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 131 publications
(234 reference statements)
0
7
0
Order By: Relevance
“…Indeed, rheostat positions can be likened to a volume dial on a stereo, with substitutions dialing the functional “volume” either up or down. Furthermore, substitutions at some rheostat positions modulated only a single functional parameter (e.g., K d for binding ligand) whereas substitutions at others simultaneously modulated multiple parameters (e.g., substrate affinity, K d for binding allosteric ligand, and the magnitude of allosteric coupling between them) 1,3–7 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, rheostat positions can be likened to a volume dial on a stereo, with substitutions dialing the functional “volume” either up or down. Furthermore, substitutions at some rheostat positions modulated only a single functional parameter (e.g., K d for binding ligand) whereas substitutions at others simultaneously modulated multiple parameters (e.g., substrate affinity, K d for binding allosteric ligand, and the magnitude of allosteric coupling between them) 1,3–7 …”
Section: Introductionmentioning
confidence: 99%
“…If >70% of substitutions maintain WT‐like function for all measured parameters, the position is assigned to the “neutral” category (Martin et al, 2020). If its set of substitutions samples ≥50% of the accessible functional range, the position is assigned to the “rheostat” category (Wu et al, 2019); this behavior has been observed for numerous positions in globular proteins (Bantis et al, 2020; Fenton et al, 2020; Hodges et al, 2018; Meinhardt et al, 2013; Ruggiero et al, 2021; Swint‐Kruse et al, 2021; Tang et al, 2017; Tang & Fenton, 2017; Wu et al, 2019). If >64% of substitutions abolish function, the position is assigned to the “toggle” category (Miller et al, 2017); this textbook substitution behavior is frequently observed at important, conserved positions in globular proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In other proteins, the full tuneable range can be accessed by a variety of single substitutions (e.g., Tang & Fenton, 2017). Furthermore, in some globular proteins, 50%–100% of the tuneable, functional range can be sampled by a set of substitutions at an individual “rheostat” position (e.g., Bantis et al, 2020; Campitelli et al, 2020, 2023; Fenton et al, 2020; Page et al, 2022; Ruggiero et al, 2021; Swint‐Kruse et al, 2021; Wu et al, 2019). It is still unknown whether the existence of rheostat positions requires a classically‐folded protein structure or whether they can also be present in intrinsically disordered regions (IDRs).…”
Section: Introductionmentioning
confidence: 99%
“…If >70% of substitutions maintain WT-like function for all measured parameters, the position is assigned to the “neutral” category. 57 If its set of substitutions samples ≥50% of the accessible functional range, the position is assigned to the “rheostat” category; 2 this behavior has been observed for numerous positions in globular proteins 13 ; 5; 6; 9; 38; 58; 59 . If >64% of substitutions abolish function, the position is assigned to the “toggle” category; 60 this textbook substitution behavior is frequently observed at important, conserved positions in globular proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In other proteins, the full tuneable range can be accessed by a variety of single substitutions (e.g., 1 ). Furthermore, site-saturating and semi-saturating mutagenesis (SSM and semiSM, respectively) of single positions revealed that, in some globular proteins, substituting individual "rheostat" positions can sample 50-100% of the tuneable functional range (e.g., [2][3][4][5][6][7][8][9] ). It is still unknown whether a classically folded protein structure is a pre-requisite for the presence of rheostat positions or whether they can also be present in intrinsically disordered regions (IDRs).…”
Section: Introductionmentioning
confidence: 99%